Comparison of Pelvic Organ Prolapse and Sexual Function After Vaginal Natural Orifice Transluminal Endoscopic Surgery and Conventional Laparoscopic Hysterectomy - Haliscelik, Mesut Ali; Sanli, Cengiz; Bala, Mesut; Erdem, Selami; Can, Behzat; Bagli, Ihsan; Kavak, Salih Burcin (Mdpi, 2025)
Aim: In our study, we aimed to comprehensively evaluate the surgical parameters of patients who underwent total laparoscopic hysterectomy (TLH) and vaginal natural orifice transluminal endoscopic surgery (vNOTES) hysterectomy and their effects on the development of pelvic organ prolapse (POP) and sexual function one year later. Materials and Methods: This retrospective and comparative study involved a review of medical records for 42 patients who underwent total laparoscopic hysterectomy (TLH) for benign conditions and 42 patients who underwent hysterectomy using vaginal natural orifice transluminal endoscopic surgery (vNOTES) at our clinic between January 2023 and January 2024. Evaluations of preoperative and postoperative pelvic organ prolapse and sexual function were conducted, and the anatomical and functional outcomes of both surgical methods were compared. Results: In this study, there was no statistically significant difference between the groups in terms of age (p < 0.299), BMI (p < 0.819), parity (p < 0.615), surgical indications and menopausal status (p < 0.535) (p > 0.05). The vNOTES method was found to be significantly shorter than TLH in terms of surgical time (vNOTES: 58 min, TLH: 80 min, p < 0.001). However, there was no significant difference between the two methods in terms of preoperative and postoperative hematocrit values, hospital stay and FSFI scores (p > 0.05). Among the POP-Q parameters, a significant difference was observed only in the Aa parameter in favor of the vNOTES method (p < 0.003). Conclusions: In our study, the vNOTES method provided a shorter surgical time and better anterior vaginal support compared to TLH, but both methods offered similar results in terms of sexual function. More comprehensive studies are needed to clarify the long-term effects.
Keywords: hysterectomy; laparoscopy; female sexual function index; pelvic organ prolapse